Characterization of Carambola (Averrhoa carambola L.) Plant Collection of Cibinong Plant Germplasm Garden Based on Phenotypic and Genetic Characters - Dody Priadi; Ambar Yuswi Perdani; Yuli Sulistyowati; Fiqolbi Nuro Pohan; Enung Sri Mulyaningsih (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Indonesia as a rich biodiversity country has many superior fruit plant germplasms such as sweet star fruit or carambola (Averrhoa carambola L.). Some varieties of carambola which collected at the Germplasm Garden of Research Center for Biotechnology-LIPI have been used for parent trees of fruit plant production. Therefore, they have to be characterized both phenotypically and genetically. The objective of the study was to analyze the relationship between eight varieties of carambola i.e. Malaysia, Penang, Rawasari, Bangkok, Sembiring, Dewabaru, Demak and Dewimurni at the germplasm garden based on phenotypic and genetic characters. Phenotypic characters were observed directly in the field, whereas genetic characters were observed with RAPD markers using 10 primers. Phylogenetic analysis was done using NT-SYS software showed that there were three clusters of carambola varieties. Meanwhile, Malaysia and Penang varieties have closed relationships (96%) compared with the other varieties. The result of the study would be dedicated to updating and completing the existing fruit plant collection database of Plants Germplasm Garden.